The Princeton Seminary bulletin. - Princeton Theological Seminary ([Princeton, N.J.], [Princeton Theological Seminary], 1907)
Vols. for 1907/1908-1936/1937: no. 1, Commencement issue, no. 2, Necrology report, no. 3, News, no. 4, Catalogue; v. for 1937/1938-1938/1939: no. 1, 3, News, no. 2, Bulletin of courses, no. 4, Catalogue; v. for 1939/1940-1944/1945: no. 1, 4, News, no. 2, Bulletin of courses, no. 3, Catalogue; v. for 1945/1946: no. 1, Bulletin of courses, no. 2, 4, News, no. 3, Catalogue; v. for 1946/1947-<1952/1953>: no. 1, 3, 4, News, no. 2, Catalogue.
1920/1921 has 5 nos.; 1933/1934, no. 2-3 not published; 1935/1936, no. 3 not published; 1936/1937, no. 2 not published; 1943/1944, no. 4 not published.
Also issued on microfilm by American Theological Library Association.
SERBIB/SERLOC merged record
Keywords: Princeton Theological Seminary; Princeton Theological Seminary; Periodicals